Zola, Lourdes and the New Religious Crowd in Ideological Debates in Portugal (1894-1932) - Eduardo Cintra Torres (Conserveries Mémorielles)
The impact of Émile Zola’s novel on Lourdes was felt in Portugal even before its publication in France in 1894. The naturalist writer’s documentary fiction plucked a central chord in the political and religious debate of the time, particularly the dichotomy between science and religion, the renewal of faith and the legitimacy of the crowd in public spaces. This paper deals with only one aspect of that debate, active in Portugal between 1894 and 1932 – the impact of Zola´s innovative thesis about Lourdes’ new religious crowd and ‘the crowd’s healing power’. The development of the debates shows how Catholic sectors increasingly incorporated the ‘crowd’ into renewed Catholicism, especially after the Fátima events of 1917, while the liberal bourgeoisie continued to reject the masses.